Peran Self-compassion Terhadap Resiliensi Penyandang Disabilitas Fisik: Penelitian - Vivin; Hasnida; Josetta M. R. Tuapattinaja (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the role of self-compassion in predicting resilience among individuals with physical disabilities. People with physical limitations often experience psychological stress, social challenges, and environmental barriers that may hinder their ability to adapt. Self-compassion, defined as treating oneself with kindness and without self-judgment, is believed to be an important internal factor that supports resilience in challenging situations. This research employed a quantitative approach with a linear regression design and involved 387 participants recruited through snowball sampling. Data were collected using the Indonesian adaptations of the Connor-Davidson Resilience Scale (CD-RISC 25) and the Self-Compassion Scale (SCS). The results indicate that self-compassion has a significant and positive effect on resilience (p < 0.05), contributing 73.6% to its variance. These findings suggest that higher levels of self-compassion are associated with greater resilience, enabling individuals with physical disabilities to cope with stress and adapt to their limitations more effectively.